Kajian Aktivitas Antioksidan Kacang Gude (Cajanus cajan) dan Pengaruhnya Terhadap Aktivitas Enzim Hati Tikus Yang diinduksi Karbon Tetraklorida - Roosmarinto Roosmarinto; Muji Rahayu (POLTEKKES KEMENKES YOGYAKARTA, 2016)
Legumes bean is a plant that is rich in compounds called polyphenols, especially flavonoids. Pigeon pea is a legume species that has purple-black skin, contains various compounds, among others, polyphenols, anthocyanins, and flavonoids. Polyphenol, anthocyanins, and flavonoids compounds have an antioxidant activity of endogenous antioxidants which can help to fend off free radicals that occur in the body. The antioxidant activity of pigeon pea (Cajanus cajan) in vitro has measured using DPPH method and obtained results of IC50 value of 70.32 mg/ml. Pigeon pea beans contain anthocyanin compounds of 208.307 mg / 100 g. Measurement of antioxidant activity pigeon pea in vivo was performed by animal model white rats Wistar male as many as 25 animals that were divided into 5 groups. Each experimental group consisted of 5 mice, the group N as a normal control group, the group S as a pain control, the group G1, G2, and G4 were given bean powder pigeon pea respectively 100, 200 and 400 mg / bwt with sonde, for 14 days , S group, G1, G2 and G4 induced by carbon tetrachloride with intraperitoneal administration. After 24 hours, the blood of all rats was taken through vena orbitalis and then the activity of AST, ALT and GGT enzymes and levels of malondialdehyde (MDA) were determined. The result of this study showed inhibition of the increase in the activity of AST, ALT and GGT enzymes and MDA levels in rats fed with powdered pigeon pea. From these results, it can be concluded that pigeon pea beans have antioxidant activity which is capable of preventing damage to liver cells and lipid peroxidation. A result of this study showed inhibition of the increase in the activity of enzymes AST, ALT and GGT and MDA levels in rats fed powdered pigeon pea. From these results, it can be concluded that pigeonpea beans have antioxidant activity which can prevent a damage in Hepar cells and lipid peroxidase.